The impact of the market transparency unit for fuels on gasoline prices in Germany - Ralf Dewenter; Ulrich Heimeshoff; Hendrik Lüth (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2016)
Increasing horizontal as well as vertical transparency in oligopolistic markets can be advantageous for consumers, due to reduced search costs. However, market transparency can also affect incentives to deviate from collusive agreements and the punishment by rival firms in the market. Using a panel of 27 European countries, we analyze the impact of increased market transparency via the introduction of a market transparency unit for fuels in Germany. Applying a difference-in-differences approach, we find evidence that both gasoline and diesel prices have increased. While consumers may be better off using a retail price app for fuels, gas stations are also able to compare prices at almost no cost.
Keywords: 330; market transparency unit; regulation; fuel prices; difference-in-differences